Make your web site work for you : how to convert your online content into profits - Cannon, Jeff. (New York : McGraw-Hill, 2000)
This book is divided into seven parts: The basics; The first step to going online: Developing a brand; Building online content to drive your business; Driving traffic and keeping it in your online store; Preparing your site to profit; Research and customer service to enhance communications; and Case studies.
Keywords: Marketing; Internet marketing; Electronic commerce; Internet advertising; Internet marketing; Internet advertising; Electronic commerce